(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2019)
The paper is devoted to questions on increasing of noise immunity of GPS/INS navigation systems containing GPS and inertial navigation systems. Analysis of effectual methods for digital processing of noisy signals of GPS/INS navigation systems is actual task. At the same time there is another direction of development of GPS navigation systems, based on modification of aerial tract and filtration devices. Different adaptive methods of multi-aerial receipt can be stressed out as an example. As regards the filtration method, there are some additional possibilities for filtration of noisy GPS signals upon presence of a priory or a posteriori data on energy-frequency characteristics of noise signal. The comparative analysis of methods for increasing of noise immunity of integrated GPS/INS navigation systems is carried out. The possibility for optimization of averaged integrated value of modified indicator, named as effective ratio of power of carrier signal on noise power regarding the case of utilization of noise signals pertaining to broad class of noise signals characterized by presence of integrated limitation condition imposed on amplitude-frequency spectrum. The optimization task on increase of averaged integrated parameter indicating the effective value of ratio of power of carrier signal on power of noise signal is formulated. Solution of formulated optimization task make it possible to formulate recommendations for increasing the noise immunity of GPS/INS based navigation systems for some limited class of utilized jamming noise. The methodic to increase noise immunity of GPS targeting systems in condition of jamming noise is suggested.